ISOTOPIC EQUILIBRATION AGE OF Sm-Nd WHOLE-ROCK SYSTEM IN THE NAPIER COMPLEX (TONAGH ISLAND), EAST ANTARCTICA - オワダ, マサアキ; オサナイ, ヤスヒト; カガミ, ヒロオ; OWADA, Masaaki; OSANAI, Yasuhito; KAGAMI, Hiroo (National Institute of Polar Research, 1994)
P(論文) Whole-rock measurements of ^<143>Nd/^<144>Nd and ^<147>Sm/^<144>Nd are reported for gneisses which had undergone granulite-facies metamorphism in Tonagh Island from the Napier Complex, East Antarctica. Felsic and ultramafic gneisses in adjacent outcrops yield a well-defined isochron age of 2458±61 Ma with an initial ratio of 0.50897±0.00004 (initial εNd=-9.5±0.7). These gneisses show a granuloblastic microfabric overprinted by a pervasive intercrystalline texture. The negative εNd value suggests that the isochron age indicates re-equilibration of the isotopic system on a whole-rock scale at 2458±61 Ma. On the other hand, mafic gneisses which crop out as thin layers alternated with pelitic and felsic gneisses yield an isochron with an age of 3708±533 Ma. The mafic gneisses display a uniform granuloblastic texture. The age of 3708 Ma is older than c. 3070 Ma, which has been regarded as the earliest tectonothermal age in the complex. εNd values at 3708 Ma for individual mafic gneiss range from +1.3 to +3.3. The values are within the range of Archaean komatiites and basalts, suggesting that the mafic gneisses were derived from the depleted mantle at c. 3700 Ma. departmental bulletin paper